JENIS PAKAN DAN PERILAKU MAKAN MONYET EKOR PANJANG (Macaca fascicularis) DI ZONA PEMANFAATAN PULAU SATONDA TAMAN NASIONAL MOYO SATONDA - Chatami, Lalu Radinal Ihya; Syaputra, Maiser; Hadi, Islamul (AGROTEKSOS; Vol 34 No 1 (2024): Jurnal Agroteksos April 2024DO - 10.29303/agroteksos.v34i1.973, 2024)
Satonda Island, which is located in Dompu Regency, West Nusa Tenggara Province, is a habitat for long-tailed monkeys. This research aims to determine the type of food and eating behavior of long-tailed monkeys in the utilization zone of Satonda Island. The method used in this research is Focal animal sampling with the alpha long-tailed monkey as the research object. The results of the research show that there are 8 types of food sources for long-tailed monkeys in the utilization zone of Satonda Island, Moyo Satonda National Park, consisting of figs ( fig tree ), sour ( Tamarindus indica ), offerings ( Lannea coromandelica ), ivory coconut ( Cocoa nuts ), cherries ( Muntingia calabura ), ketapang ( Terminalia catappa ), lantana ( Lantana montevidensis ), and hibiscus ( China rose ). Acid is the most consumed feed with a percentage of 22.67%. The most eaten part is fruit with a percentage of 42%. Meanwhile, the eating behavior of long-tailed monkeys that appears most often is chewing with a percentage of 30.7%, and swallowing behavior is the least common eating behavior with a percentage of 20.4% in observations of eating behavior   Keywords: Types of food, long-tailed monkeys, feeding behavior, Satonda Island.